Strategi Wakil Kepala Madrasah Bidang Kesiswaan dalam Meningkatkan Disiplin Siswa di MA Ihyaul Ulum Dukun Gresik - Dian Fatma; Hasyim Rosyidi; Muhammad Haris (Program Studi Manajemen Pendidikan Islam, Fakultas Tarbiyah, Institut Pesantren Sunan Drajat Lamongan, 2021)
Disciplinary behavior of students is strongly influenced by several factors, namely; neighborhood, family and school. In this case, the madrasa becomes the baton from the family to train students discipline, because students who have a disciplined attitude will tend to grow a sense of responsibility in doing something and be able to respect and obey a rule. Students who have a disciplined attitude can become students who are faster in developing and improving their achievements, and become students who obey the rules so as to create a conducive learning atmosphere. In responding to this, the deputy head of the student madrasa of course has a strategy that he applies in improving student discipline at MA Ihyaul Ulum so that all students in the madrasa are able to become students who obey the rules that apply in the madrasa and become students who have awareness of discipline research objectives 1) To determine the strategy of vice principal in the field of student affairs in improving student discipline in MA. Ihyaul Ulum Dukun Gresik 2) To find out the supporting factors and inhibiting factors for the vice principal of student affairs in improving student discipline at MA Ihyaul Ulum Dukun Gresik this study used a qualitative approach and the type of this research was field research (Field Research) the results of the research on the strategy of the vice principal for student affairs in improving student discipline at MA Ihyaul Ulum Dukun Gresik by a) Setting an example in being disciplined b) Both educators and students must comply with all applicable rules at the madrasa c) Implement a point system in any violation d) Cooperate with the BK teacher and all teachers e) Consistent in enforcing student discipline. f) Build communication with students, teachers and community and Characteristics of Student Discipline at MA Ihyaul Ulum Include the following: a) Discipline of student dress b) Discipline of punctuality c) Discipline of social behavior d) Discipline in learning ethics e) Discipline of following the congregation of dhuha prayers f) Discipline following congregational dhuhur prayer g) Discipline following the study/recitation of the book and dhikr after the dhuha prayer.